The cost of credit in the micro-finance industry in South Africa - Campbell, Jonathan (Rhodes University, Faculty of Law, Law, 2007)
This thesis analyses the cost of credit in the micro-finance industry in South Africa. The study situates micro-lending agreements within the law of contract, beginning with an examination of contractual fairness in terms of the common law: the fundamental principle of freedom of contract that underpins the common law of contract; the principle that agreements contrary to public policy should not be enforced; and the impetus given by constitutional values that inform public policy. In regard to moneylending transactions, common law usury law will be explained. The study then goes on to trace the origins and rapid growth of the micro-finance industry which was made possible by its exemption in 1992 from the Usury Act 73 of 1968. The upshot of this development was that registered micro-lenders have for nearly 14 years charged excessive interest rates, and continue to do so. The dire socio-economic impact of these high interest rates on individual consumers and lowincome communities is then demonstrated: how borrowers of small loans soon become over-indebted; the loss of billions of rands every year to low-income communities in the form of interest on micro-loans. The study then shifts to the legislative response to the need for consumer protection in regard to consumer credit. The extensive credit law review process is explained, resulting ultimately in the National Credit Act 34 of 2005, which allows the Minister to prescribe limits on interest rates and fees in all sectors of the consumer credit market. The prescribed limits on the cost of credit in the micro-finance sector are thoroughly explained and analysed, with particular reference to the implications of each element of the credit costing structure, and the combined impact of the total cost of credit on different types and sizes of loans. The envisaged maximum interest and fees will markedly alter the positions of micro-lenders and consumers, and receive careful analysis. The study closes with a summary of findings in the thesis, which includes suggested amendments to the National Credit Regulations and a review of possible legal challenges to the high cost of credit on smaller loans.
Keywords: Contracts -- South Africa; Credit -- Law and legislation -- South Africa; Microfinance -- South Africa; Usury laws -- South Africa